ANALISIS PENENTUAN INDIKATOR UTAMA PEMBANGUNAN SEKTOR PERTANIAN DI INDONESIA: PENDEKATAN ANALISIS KOMPONEN UTAMA - SAKTYANU K. DERMOREDJO (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
One of the main problems in recent agricultural development is difficulty in gettingfast, accurate information. This indicators choice is important to guide the government inimplementing agricultural development successfully. This paper aims at obtaining the mainindicators explaining agricultural development performance. Using PCA (PrincipleComponent Analysis), there were eight main indicators out of 38 variables, namely: (1)irrigated land areas growth (%/year); (2) ratio of rural/urban labor in agricultural sector; (3)ratio of rural/urban labor in non-agricultural sector; (4) Food Security Index (energy andprotein) trend; (5) Agricultural sector’s GRDP growth (%/year); (6) Agricultural sector’sshare in GRDP (%/year); (7) use of agricultural inputs (seed, fertilizer, and pesticide); and(8) farm business productivity. The results showed that farmers’ incomes and agriculturalcommodities’ competitiveness (based on export and import trends) were not the mainindicators of agricultural development. Therefore, targets of agricultural development arenot farmers’ incomes improvement, but farm business productivity improvement throughincrease in agricultural inputs use.